Unconventional control solutions for small fixed wing unmanned aircraft. (October 2018) - Panta, A.; Mohamed, A.; Marino, M.; Watkins, S.; Fisher, A.
Abstract: Micro Air Vehicles (MAVs) have the potential to revolutionize our capabilities in gathering information, monitoring situations, and surveillance. They are required to maneuver in and around obstacles as well as negotiate atmospheric disturbances whilst holding accurate trajectories and minimizing rotation which can blur imagery. A study of existing literature on MAV control challenges found that current turbulence mitigation systems and control surface configurations lack the speed of response and control authority required to maintain steady flight in turbulence. Improved control response may come from unconventional designs, bio-inspired systems, or from careful manipulation of the flow mechanics. As such, in this paper, key unsteady aerodynamic parameters are also reviewed and considered prior to deriving potential control solutions that could help MAVs fly well in turbulence.